Determination of Capacities of Eccentric Stiffeners Part 2: Analytical Studies - Alvarez Rodilla, J.; Kowalkowski, Keith (Engineering Journal, 2021)
Analytical investigations were performed on column specimens with an effort to evaluate the effective stiffener capacity of eccentric stiffeners when used within moment connections of beams connecting to column flanges. First, analytical models were developed for the experimental column specimens presented in the companion paper Part 1: Experimental Studies (Alvarez Rodilla and Kowalkowski, 2021). These models were utilized to calibrate the finite element methodology and to develop consistent comparisons between the experimental and analytical results.Finite element models were then developed for larger column sizes more regularly used in practice. In all, 148 models were developed to represent W14×68, W14×120, W14×176, W14×233, W24×131, and W24×229 column specimens. The column models utilized a similar setup to experiments and were subjected to three different loading conditions described as (1) single tension with load pulling away from the column specimen; (2) single compression with load applied toward the column specimen; and (3) double compression with loads applied on both flanges, directly opposite of each other. Parameters also included the unsupported length and stiffener thickness for single compression, the stiffener thickness for double compression, and the weld size/loading plate thickness for single tension. For all test methods and each set of parameters, a group of four column specimens consisted of (1) one modeled without stiffeners, (2) one modeled with concentric stiffeners, (3) one modeled with stiffeners at an eccentricity of 2 in., and (4) one modeled with stiffeners at an eccentricity of 4 in.